PENERAPAN BUDAYA ANTRI DALAM MENINGKATKAN SOSIAL EMOSIONAL ANAK USIA DINI - Siska Ayunita; Khadijah Khadijah; Emilia Fitri Harahap; Nurhaliza Hakim (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
This study is to determine the increase in discipline in queuing culture in children, through routine activities, spontaneous activities, exemplary and programmed activities. This research uses a qualitative approach. This type of research is a descriptive approach research. Based on the focus of research and data sources, the data collection techniques used in this study are observation, interview and documentation methods. The surrounding environment is very influential in supporting queuing habits in children. One way to teach queuing to children is through early habituation and starting consistently in the family environment and school environment. The positive impact of queuing / waiting for turns for children's development includes increasing discipline. In addition, implementing a queuing culture can provide positive things, namely learning to be patient in terms of waiting and learning about the shame of grabbing. This study was conducted to find out how disciplined children are towards queuing culture carried out by children at school.